Wake up and smell the organic coffee - Bafana, Busani (2019)
Dorianne Rowan-Campbell is an organic coffee farmer in Jamaica. Taking over her father’s farm in 1992 and turning it into an organic one was a huge risk at the time. However, she sustainably grows 1,800 coffee trees and harnesses nature to deal with pests, rather than using pesticides